Using wordlists to teach and learn Arabic vocabulary - Haslina, Hassan; Khadijah Khalilah, Abdul Rashid; Mohd Feham, Mohd Ghalib (2015)
This paper reports on a project that developed a specialized corpus of written Arabic texts in Malaysia and highlights its wordlist. A corpora and sub-corpora made of Arabic textbooks for secondary schools in Malaysia were developed by using Sketch Engine, a corpus software. A master wordlist of all textbooks used in form one up to form five were generated. Apart from that, a wordlist of textbooks for each form was also produced. Based on the sub-corpora of the textbooks, wordlists of verbs, nouns, and particles were generated separately for each form. This means each form has its own wordlists. The aim of this study is to introduce a new approach to teaching non-native Arabic speakers who learn Arabic in a non-native-Arabic speaking environment. Wordlists can be used to engage students in vocabulary learning and to develop their interest to learn words based on its context or to be more specific from their own textbooks. Referring to the wordlists is another way for the teachers and the students alike to check whether the later are picking up the vocabulary that they are expected to learn at a certain level. The wordlists also aid the students in understanding their lessons better. The corpus of this study is aimed at being a source of reference for language research and development as well as in the teaching and learning of the Arabic language. Keywords: Arabic vocabulary, corpus, textbooks